Analytical HPLC Method for Determination of Miconazole Nitrate and Eugenol in Formulated Emulgel - Zanwar, Aarti S. (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: Conventional antifungal medications face challenges, such as recurrence of infection, medication resistance, and drug-related toxicity. Biofilm-associated cells exhibit resistance due to drug-efflux pumps and metabolic conditions. A new formulation containing miconazole nitrate (MIZ) (antifungal drug) and eugenol (EUL) (antibiofilm agent) increases the effectiveness of antifungal activity. This necessitates a new high-pressure liquid chromatography (HPLC) method to develop for quality control analysis. Materials and Methods: The proportion of solvent (acetonitrile: methanol:ammonium acetate buffer, pH 6.5) in the ratio of 25:55:20 v/v/v resolved the cited drugs on the C8 column at 238 nm by the HPLC method. The developed method was validated as per the International Council for Harmonisation Q2 guideline for different parameters. Result and Discussion: The linearity and range for MIZ (50–250 μg/mL) and EUL (26.5–132.5 μg/mL) solution were performed by the mentioned HPLC method. The interferences of the excipients, MIZ and EUL, were negligible, as the recovery percentage ranged from 98.867% to 101.482%. The quantified drug content was determined to be 98.450 ± 1.303 for MIZ and 97.467 ± 1.250 for EUL by the developed and validated HPLC method. Conclusion: The proposed research was appropriate for the examination of MIZ and EUL content in the formulated emulgel by the developed HPLC method.